A Compact, Portable Device for Microscopic Magnetic Imaging Based on Diamond Quantum Sensors - Alex Shaji; Kevin J. Rietwyk; Islay O. Robertson; Philipp Reineck; David A. Broadway; Jean‐Philippe Tetienne (Advanced Sensor Research)
Abstract Magnetic imaging based on ensembles of diamond nitrogen‐vacancy quantum sensors has emerged as a useful technique for the spatial characterization of magnetic materials and current distributions. However, demonstrations have so far been restricted to laboratory‐based experiments using relatively bulky apparatus and requiring manual handling of the diamond sensing element, hampering broader adoption of the technique. Here a simple, compact device that can be deployed outside a laboratory environment and enables robust, simplified operation is presented. It relies on a specially designed sensor head that directly integrates the diamond sensor while incorporating a microwave antenna and all necessary optical components. This integrated sensor head is complemented by a small control unit and a laptop computer that displays the resulting magnetic image. The device is tested by imaging a magnetic sample, demonstrating a spatial resolution of 4 µm over a field of view exceeding 1 mm, and a best sensitivity of 45 µT Hz−1 per (5 µm)2 pixel. The portable magnetic imaging instrument may find use in situations where taking the sample to be measured to a specialist lab is impractical or undesirable.